Analysis of Legal Factors Related to Drug Security in Thailand: Scoping Review - Rutjanathamrong, Parun; Sooksriwong, Chaoncin; Kasemsap, Vijj; PiPattanachat, Vasin; Usavakidviree, Vinit; Kijtiwatchakul, Kannikar (Princess of Naradhiwas University Journal, 2025)
The United Nations Sustainable Development Goals (SDGs) related to health and well-being are closely connected to drug security, which in this study refers to “available when in need” for both normal and emergencies. This study was secondary research, employing a scoping review methodology to gather data on the legal factors affecting drug security issues in Thailand from January 1, 2000 to August 31, 2024. The data was gathered from academic databases and evaluated using the PRISMA-Scr Flow Diagram, alongside an exploration of legal awareness related to drug security through the Newscenter X news database. This study identified that the main issues affecting drug security in Thailand include reliance on imported pharmaceutical raw materials, inefficient management of the drug supply chain, the complexity of laws related to patents, trade competition, and international trade, which obstruct the production and access to generic drugs. Additionally, the system for procuring and supplying medicines during emergencies has proven inadequate in meeting demand promptly. Existing laws and measures require improvement to ensure drug security. The key recommendations from this study include the development of a new legal framework to support domestic drug production, procurement systems efficiency for greater flexibility and speed, and implementing compulsory licenses under patent laws when necessary to enhance access to affordable medicines for the people.